Productivity, profitability, quality and nutrient uptake of heat tolerant wheat (Triticum aestivum) cultivars as influenced by staggered sowing and nutrition levels - PRASAD, SHAMBHU; AGRAWAL, K K; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2019)
In the present investigation, we investigated the effects of staggered sowing and nutrition levels on productivity, profitability, quality and nutrient uptake of heat tolerant wheat (Triticum aestivum L.) cultivars during rabi season of 2014-16 at the Breeder Seed Production Unit, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh. Soil of the experimental plot was clay in texture, medium in organic carbon and available NPK with neutral pH (7.4). Experiment was laid out in split-plot design with three replications. The main plots consisted of three staggered sowing, i.e. 30th November, 20th December and 10th January and three nutrition levels, viz. RDF (120:60:40 kg NPK/ha), 20% higher RDF and 20% lesser RDF, while three heat tolerant varieties, viz. MP 1203, MP 3336 and GW 173 were allotted in sub-plot. Results revealed that among the sowing time, grain yield (4.20 t/ha), straw yield (5.04 t/ha), biological yield (9.25 t/ha) and harvest index (45.3%) had recorded significantly higher in 30th November sowing. Crop sown on 30th November had increased the grain yield by 11.7 and 37.7% over that of 20th December and 10th January sowing, respectively. Among the nutrition levels, 20% higher RDF had recorded significantly higher grain yield (4.01 t/ha), straw yield (4.84 t/ha), biological yield (7.78 t/ha) and harvest index (45.1%) compared to RDF and 20% lesser RDF. Application of 20% higher RDF increased the grain yield to the tunes of 9.8 and 19.7% compared to RDF and 20% lesser RDF, respectively. Significantly higher grain yield was recorded with MP 3336 (4.05 t/ha) compared to MP1203 (3.59 t/ha) and GW173 (3.36 t/ha). Crop sown on 30th November had significantly higher gross returns (` 79218/ ha), net returns (` 55873/ha) and B:C ratio (3.39), respectively. Application of 20% higher RDF had maximum gross returns (` 75684/ha), net returns (` 51360/ha) and B: C ratio (3.11), respectively. MP 3336 had higher gross returns (` 76634/ha), net returns (` 53289/ha) and B: C ratio (3.28). Sowing on 30th November had significant superiority in nutrient content (NPK) in grain and straw as well as their uptake by crop. These attributes had significantly higher with application of 20% higher RDF. MP 3336 had higher NPK contents in grain and straw than that to MP 1203 and GW-173. Protein content had higher in 30th November sowing (16.01%). Application of 20% higher RDF had better protein content (15.43%). MP 3336 had markedly higher protein content (15.63%). Carbohydrate equivalent and carbon output had higher when crop sown on 30th November (3.0 and 4.1 /ha) along with 20% higher RDF (2.9 and 3.7 t/ha) in MP 3336 (2.9 and 4.0 t/ha), respectively. Therefore, sowing of heat tolerant wheat cv. MP 3336 on 30th November along with application of 20% higher RDF were proved the most ideal approach to achieve the higher productivity, profitability and nutrient uptake under the irrigated ecosystem of Madhya Pradesh.